Black Seedcoat Pigmentation Is a Marker for Enhanced Nodulation and N2 Fixation in Bambara Groundnut (Vigna Subterranea L. Verdc.) Landraces - Puozaa, Doris K.; Jaiswal, Sanjay K.; Dakora, Felix D. (Frontiers in Agronomy, 2021)
Field studies on the effect of differing seedcoat colour on plant growth and symbiotic performance of three Bambara groundnut landraces using the 15N natural abundance technique and ureide analysis in the xylem stream and petiole extracts revealed a consistent pattern in nodule function between ureide levels and shoot δ15N values, as well as between ureide levels and percent N derived from fixation at Gbalahi, Kpalisogu and Manga. At those three sites, where shoot δ15N was low and percent N derived from fixation high, ureide concentrations in the xylem sap and petiole extracts were also high, indicating that the two techniques were comparatively quite robust in estimating N2 fixation at a higher precision in the test Bambara groundnut landraces. A comparison of the effect of differing seedcoat pigmentation on the concentration of phenolics released by imbibed seeds showed that the Black landrace contained higher levels of flavonoids and anthocyanins, followed by the Red, and lowest in the Cream landrace. The Black landrace also recorded much higher nodule number and nodule fresh weight per plant, greater shoot biomass, lower shoot δ15N values, greater N derived from fixation, higher symbiotic N contribution, and increased water-use efficiency across all the five study sites, followed by the Red landrace, which produced the highest grain yield. Black seedcoat pigmentation in Bambara groundnut is therefore a marker for increased nodulation, N2 fixation and plant growth that can be tapped in breeding programs for developing high N2-fixing, water-use efficient grain legumes for use by farmers in Africa.